UMUR DAN TINGKAT PENDIDIKAN IBU HAMIL TRIMESTER I DENGAN KEJADIAN ANEMIA - Ely Tjahjani (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2017)
Anemia is a condition of decreased hemoglobin levels, hematocrit, and the number of red blood cells below normal values. Based on the data obtained at BPS Zulfiah Surabaya, it was found that there was a tendency to increase the incidence of anemia in first trimester pregnant women starting in 2013 at 34.85%, in 2014 at 36.63%, and in 2015 at 41.17%. The purpose of this study was to find out the relationship between age and education level of first trimester pregnant women with the incidence of anemia in BPS Zulfiah Surabaya in 2016. Method: The research method used was cross sectional analytic type with secondary data in 2016 at BPS Zulfiah Surabaya. The population of 226 people and a large sample of 69 people was selected by systematic random sampling. The results of the study were made frequency tables, cross tabulations, and analyzed by chi-square test. Results: The results showed that the first trimester of pregnant women in BPS Zulfiah Surabaya in 2016 had no anemia as many as 39 people (56.55%), aged 20-35 years as many as 23 people (69.70%) and higher education levels as many as 28 people (68.29%). From cross tabulation, pregnant women aged <20 years and <35 years had more anemia as many as 20 people (55.56%), and pregnant women with low education who had anemia were 17 people (60.71%). The chi-square test results found that the age variable> (18.76> 3.84) while the education level variable> (44.49> 3.84) which means H0 is rejected. Discussion: There is a relationship between age and education level of first trimester pregnant women with the incidence of anemia. Therefore, counseling is needed on regular pregnancy checks during pregnancy to early detection of complications in pregnancy as well as providing information about nutrition and how to consume the right iron tablets.